Research Progress on Ferritic/Martensitic Steels for Integrated Fast Reactor Fuel Cladding - Feng Wei, Guan Songyuan, Li Junhong, Shan Pengzhan, Xing Weiwei, Hao Xianchao, Liang Tian, Ma Yingche (Teshugang)
The integrated fast reactors use metallic fuel， with fuel cladding operating at temperatures ranging from 350 ℃ to 630 ℃ and a service lifespan exceeding 50 000 hours. As the operational cycle extends， the fast neutron irradiation dose of the cladding will increase from the current 80 dpa of MOX fuel to 150 dpa-300 dpa. Therefore， the developing new cladding materials with high thermal resistance and excellent irradiation performance has become an important part of the integrated fast reactor development. This paper summarized the background of ferritic/martensitic steels （FM steels） development， analyzed the mechanical properties and irradiation performance of various FM steels， and investigated the influence of different alloying elements on these properties. Based on these analyses， alloy optimization strategies for FM steels suitable for integrated fast reactor fuel cladding were proposed. The optimization strategy was initially modified for HT9 steel， and the modified HT9G was tested for room temperature tensile test and 700 ℃/100 MPa creep rupture life. The results show that the modified alloy exhibits excellent tensile strength and creep rupture life， its room temperature yield strength reaches 880 MPa， which is approximately 310 MPa higher than that of T91 steel and 80 MPa-120 MPa higher than that of HT9 and T92 steels. Under conditions of 700 ℃ and 100 MPa， the creep rupture life is 372 hours-385 hours， significantly exceeding the 70 hours-82 hours of HT9 under the same conditions. It shows the effectiveness of toughening design， laying the foundation for further optimization of component structural materials and enhancement of long-term durability and strength improvement.